A close look at teacher learning: Why are teachers' journeys so different?. (April 2021) - Molle, Daniella
Abstract: This paper traces the journeys of three middle-school teachers during a one-year professional development focused on the education of multilingual youth. I explore (a) how teachers' practice changed during the professional development and (b) what factors mediated these changes. The three cases illustrate different trajectories of learning: addition, transformation, and fine-tuning. I discuss these trajectories in relation to opportunities they create for student learning. I then explore multiple factors that mediated the teachers' trajectories of learning (social, ecological, and socio-cognitive). The study contributes to the emerging literature on the learning of content-area teachers who serve multilingual youth. Highlights: Teachers follow different trajectories of change during professional development. Teachers' trajectories impact the learning to which their students have access. Social, ecological, and socio-cognitive factors influence what teachers learn.